La obesidad infantil es un problema social y educativo que se debe trabajar desde las familias (VITAL, 2024)
In an interview with Dr. Liliana Mejía de Beldjenna, pediatric endocrinologist at the Children's Clinic Club Noel and Valle del Lili Foundations in Cali, professor of the pediatrics postgraduate program at the Universidad Libre, member of the GRINPED research group and former president of the Colombian Association of Pediatric Endocrinology College, the subject will be discussed in detail, as well as her love for birds, another facet of her life. We talked with her about the relevance of healthy habits to prevent childhood overweight and obesity.